2011
DOI: 10.1259/bjr/31561378
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion MRI findings of cytomegalovirus-associated ventriculitis: a case report

Abstract: Cytomegalovirus (CMV) ventriculoencephalitis is a rare but serious potential complication of CMV infection in immunocompromised patients. Characteristic diffusion-weighted imaging findings can be helpful for the diagnosis of CMV ventriculitis, as in this case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…In normal fetuses, ADC values have been shown to decrease with brain maturation, mostly due to the ongoing process of myelination, while ADC values may either increase or decrease in various fetal and pediatric brain pathologies. Previous publications dealing with the use of DWI in CMV‐infected brains include a case report by Seok et al , which showed reduced ADC values in lesions along the lateral ventricles in an adult brain, and a report by van der Voorn et al , who found elevated ADC values in their pediatric population, and attributed this to extensive tissue damage. Our findings of reduced ADC values in the subcortical white matter as well as in the thalamus, but not in the basal ganglia, pons and cerebellum, are rather intriguing.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In normal fetuses, ADC values have been shown to decrease with brain maturation, mostly due to the ongoing process of myelination, while ADC values may either increase or decrease in various fetal and pediatric brain pathologies. Previous publications dealing with the use of DWI in CMV‐infected brains include a case report by Seok et al , which showed reduced ADC values in lesions along the lateral ventricles in an adult brain, and a report by van der Voorn et al , who found elevated ADC values in their pediatric population, and attributed this to extensive tissue damage. Our findings of reduced ADC values in the subcortical white matter as well as in the thalamus, but not in the basal ganglia, pons and cerebellum, are rather intriguing.…”
Section: Discussionmentioning
confidence: 43%
“…Two studies on ADC values in CMV‐infected brains have been published to date: one was a case report that indicated a low ADC value along the ventricular walls of a CMV‐infected 20‐year‐old patient, and the other was a study performed on a pediatric population with congenital CMV infection. Recent work from our department has shown preliminary indications of a decrease in ADC values throughout the CMV‐infected fetal brain.…”
Section: Introductionmentioning
confidence: 99%
“…Before the onset of CMV CNS disease, all of these cases were diagnosed with 7 recurrent CMV viremia and had received antiviral therapy. Ventriculoencephalitis is the most common form of CMV CNS disease, but it occurs in <1% of all CMV infections [19], and it is found by autopsy in 33% of acquired immunodeficiency syndrome (AIDS) patients [20], but only rarely in patients who receive HSCT.…”
Section: Clonal Expansion Of T Cells In the Skin Is The Hallmark Of Cmentioning
confidence: 99%
“…Because of the nonspecificity of MRI, the diagnosis of CMV ventriculoencephalitis must be confirmed by histological identification of inclusion-bearing cells, the so-called "Owl's eye" cells [19,23,24].…”
Section: Clonal Expansion Of T Cells In the Skin Is The Hallmark Of Cmentioning
confidence: 99%
“…However, to our regret, the spinal cord was not collected at necropsy. In humans, ventriculoencephalitis is the most common form of cytomegalovirus infection in the CNS of immunocompromised patients 5 , 6 . One of the members of the Kansai Conference on Toxicologic Pathology (KCTP) has identified a purulent ventriculitis in a Chinchilla cat.…”
Section: Ventriculoencephalitis In a Young Mousementioning
confidence: 99%